A SNARE-Like Superfamily Protein SbSLSP from the Halophyte Salicornia brachiata Confers Salt and Drought Tolerance by Maintaining Membrane Stability, K+/Na+ Ratio, and Antioxidant Machinery - Singh, Dinkar; Yadav, Narendra Singh; Tiwari, Vivekanand; Agarwal, Pradeep K.; Jha, Bhavanath (Frontiers in Plant Science, 2016)
About 1000 salt-responsive ESTs were identified from an extreme halophyte Salicornia brachiata. Among these, a novel salt-inducible gene SbSLSP, (Salicornia brachiata SNARE-like superfamily protein) showed up-regulation upon salinity and dehydration stress. The presence of cis-regulatory motifs related to abiotic stress in the putative promoter region supports our finding that SbSLSP gene is inducible by abiotic stress. The SbSLSP protein showed a high sequence identity to hypothetical/uncharacterised proteins from Beta vulgaris, Spinacia oleracea, Eucalyptus grandis and Prunus persica and with SNARE-like superfamily proteins from Zostera marina and Arabidopsis thaliana. Bioinformatics analysis predicted a clathrin adaptor complex small-chain domain and N-myristoylation site in the SbSLSP protein. Subcellular localisation studies indicated that the SbSLSP protein is mainly localised in the plasma membrane. Using transgenic tobacco lines, we establish that overexpression of SbSLSP resulted in elevated tolerance to salt and drought stress. The improved tolerance was confirmed by alterations in a range of physiological parameters, including high germination and survival rate, higher leaf chlorophyll contents, and reduced accumulation of Na+ ion and reactive oxygen species (ROS). Furthermore, overexpressing lines also showed lower water loss, higher cell membrane stability and increased accumulation of proline and ROS-scavenging enzymes. Overexpression of SbSLSP also enhanced the transcript levels of ROS-scavenging and signalling enzyme genes. This study is the first investigation of the function of the SbSLSP gene as a novel determinant of salinity/drought tolerance. The results suggest that SbSLSP could be a potential candidate to increase salinity and drought tolerance in crop plants for sustainable agriculture in semi-arid saline soil.